2012
DOI: 10.1016/j.ejvs.2012.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Results of Ex Vivo Repair and Autotransplantation in Solitary Kidneys

Abstract: In this small series of patients who underwent ex vivo repair and autotransplantation on solitary kidneys, intra-operative renal ischaemia had no detrimental effect on renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 7 publications
1
9
0
1
Order By: Relevance
“…In fact, some studies of ex vivo repair with auto-transplantation showed positive outcomes for the treatment of RAA without any renal dysfunction in cases with a solitary kidney. [ 9 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some studies of ex vivo repair with auto-transplantation showed positive outcomes for the treatment of RAA without any renal dysfunction in cases with a solitary kidney. [ 9 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…In this series, the MDRD clearance did not change between the pre-and post-operative measurements, including cases of solitary kidney, where there was no impairment of renal function. 38 Ex vivo repair also facilitates reconstruction of small branches and is feasible in almost all aneurysmal lesions, whereas unplanned nephrectomies during in situ surgery have been reported in the literature. 1 Ex vivo repair also facilitates treatment of endovascular embolization failures, which represented 11% of patients in the present study.…”
Section: Choice Of Treatmentmentioning
confidence: 99%
“…Henke et al 6 reported a 6.6% rate for unplanned nephrectomies after RAA repair, and other reports have varied from 0% to 11%. 12,14,19,21 The unpredictable complexity of the distal arterial anatomy in these more complex hilar lesions will inevitably result in some unreconstructable lesions. Despite this, no patient in the present series suffered renal failure requiring hemodialysis, and there were no mortalities.…”
Section: Discussionmentioning
confidence: 99%